307 The study design of a trial of dupilumab in adult patients with bullous pemphigoid (BP): LIBERTY-BP ADEPT. (25th January 2023) - Murrell, Dedee F; Joly, Pascal; Werth, Victoria P; Laws, Elizabeth; Mannent, Leda P; Beazley, Bethany; Dubost-Brama, Ariane; Shabbir, Arsalan
Abstract: BP is a rare autoimmune skin-blistering disorder with a profound negative impact on quality of life, associated with burdensome morbidity and possible mortality. There is a need for effective targeted therapies with a demonstrated safety profile for BP. Dupilumab is a fully human monoclonal antibody that blocks the shared receptor component for interleukin (IL)-4 and IL-13, key and central drivers of type 2 inflammation that may play a role in BP. Published case series describes the use of dupilumab in patients with BP, but it has not been formally assessed in a clinical trial for BP. We describe the design of the LIBERTY-BP ADEPT trial (NCT04206553) that aims to investigate the efficacy and safety of dupilumab in achieving sustained remission off oral corticosteroids (OCS) in patients with moderate-to-severe BP. LIBERTY-BP ADEPT is a global, randomized, double-blind, placebo-controlled, parallel-group study consisting of a 35-day screening period, a 52-week double-blind treatment period and a 12-week follow-up period. Inclusion criteria include age 18–90 years and clinical features of BP with a confirmed diagnosis based on histopathology, immunopathology, and serology. Exclusion criteria include previous treatment with IL-4 or IL-13 antagonists or systemic or medium-to-high potency topical corticosteroids within 7 days of the baseline visit. All patients receive standard OCS to control disease activity at the start of the treatment period. Post randomization, after 2 weeks of sustained remission, OCS is to be gradually tapered and discontinued as long as disease control is maintained. The primary endpoint is the proportion of patients achieving sustained remission at week 36. Key secondary endpoints include total cumulative OCS dose, percent change in weekly average daily Peak Pruritus Numerical Rating Scale (NRS) score, and proportion of patients with improved daily Peak Pruritus NRS score ≥4 from baseline to week 36. LIBERTY-BP ADEPT aims to enroll 98 patients; enrollment is ongoing and will include more than 17 sites in Europe. BP shares pathophysiological pathways with type 2 inflammatory diseases mediated by IL-4 and IL-13. The ongoing LIBERTY-BP ADEPT study is the first randomized, controlled trial designed to evaluate the efficacy and safety of dupilumab in patients with moderate-to-severe BP.